Judge Frank Creede, Jr. Swears In Superior Court Judge Mario Olmos - Watkins, Howard::::::::: (1983)
Judge Frank Creede, Jr., Judge Mario Olmos hugging his mother, Delores Olmos; son Daniel Olmos, Mario's father, Fidel Olmos, looking on Law Offices of Olmos and Frampton at 925 N St. #150, Fresno